2019
DOI: 10.1111/fare.12402
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Working Mothers Experiencing Workplace Bullying: Trauma Transferred to Young Children

Abstract: Objective To examine how workplace bullying experienced by South Korean working mothers is connected to the displacement of the mothers' anger and anxiety onto their young children. Background Workplace bullying has become a nationally and internationally recognized occupational health and safety issue in recent years. Despite an increasing number of working mothers, there is no research on the relationship between workplace bullying and working mothers' perception and experience in relation to their children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Further, regarding domestic violence and corporal punishment, it was revealed that corporal punishment among married women (more than fifty percent) causes domestic violence. In line with this study, Jahng (2020) found that married women who had experienced domestic violence. In the same way, it was also found that married women are bullied by the use of tobacco.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further, regarding domestic violence and corporal punishment, it was revealed that corporal punishment among married women (more than fifty percent) causes domestic violence. In line with this study, Jahng (2020) found that married women who had experienced domestic violence. In the same way, it was also found that married women are bullied by the use of tobacco.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of Nepal, married women have problems of forcefulness for sexual activities and other misbehaving like scolding and blaming. These cases if known by the community people, it is extremely defamed (Jahng, 2020). In general, violence is an extensively under-reported case, thus accessible figures and records are inclined to misjudge the reality.…”
Section: Introductionmentioning
confidence: 99%
“…When young workers are subjected to workplace bullying and harassment, it also impacts their families. Jahng (2020) found that when young mothers are bullied at work, it has severe spillover effects on their children, sometimes amounting to trauma. To avoid this, training and orientation materials need to highlight the organizational workplace bullying and harassment policy and where and how to seek help when these behaviours occur.…”
Section: Discussionmentioning
confidence: 99%
“…Parents who experienced bullying outside the home may replicate that behaviour at home. For example, South Korean mothers who are bullied in the workplace have negative views of parental roles and negative attitudes towards children, and they are unable to detect their children's signals of distress or needs sensitively (Jahng, 2020). Parents' workplaces can also influence peer relationships through possible family movements (Chenet al, 2006).…”
Section: Understanding Bullying From a Socio-ecological Perspectivementioning
confidence: 99%